Civil Protection Limitations for the Architectural Designer and its Effects - Alketbi, Raja; Othman, Ayaman (Journal of Legal Sciences, 2026)
The Architectural Designer, in the process of producing architectural works, needs civil protection, so that he can be creative and produce functional and aesthetic works that interact with the spatial environment. Consequently, we can find a design that meets the technical, human, and aesthetic requirements. Therefore, the UAE Federal Law No. 38 of 2021 on Copyrights and Related Rights is the most appropriate to regulate and protect this architectural art, in addition to the provisions of the UAE Civil Transactions Law No. (5) of 1985. Whenever there is an infringement on the architectural work, it is necessary to resort to the civil protection means.The study aimed to identify the civil protection of the Architectural Designer in terms of place and time, the mechanisms for protecting architectural works from infringement, and to identify the elements and effects of the civil liability lawsuit for any infringement on the rights of the Architectural Designer.The study concluded with a number of results, the most prominent of which are: The seizure of the architectural work refers to the financial right, as it is not permissible to seize the moral right. We noted that the special nature of the seizure of buildings prevents the possibility of seizing them.The study concluded with several recommendations, including: We recommend that the UAE legislator provide protection for buildings that include architectural works, in order to protect the rights of the Architectural Designer from infringement, while allowing others to view architectural works embodied in buildings and take pictures if these buildings are located in public places.